The animator's survival kit : A manual of methods, principles and formulas for classical, computer, games, stop motion and internet animators - Williams, Richard, 1933- (London : Faber, 2009)
Animation is one of the hottest and most creative areas of film-making today . During his more than 40 years in the business, Richard Williams has been one of the true innovators, and serves as the link between the golden age of animation by hand and the new computer animation successes.In this book, based on his sold-out Animation Masterclass in the United States and across Europe, Williams provides the underlying principles of animation that very animator - from beginner to expert, classic animator to computer animation whiz - needs.Using hundreds of drawings, Williams distills the secrets of the masters into a working system in order to create a book that has become the standard work on all forms of animation for professionals, students and fans.This new expanded edition includes more on animal action, invention and realism with sophisticated animation examples
"A manual of methods, principles and formulas for classical, computer, games, stop motion and internet animators."--Cover.
Previous ed.: 2001.
Title on accompanying DVD: The animator's survival kit animated.
Keywords: Animation (Cinematography).; Animation (Cinematography).; Drawing -- Technique